Algebraic Relations between Harmonic and Anti-harmonic Moments of Plane Polygons. (31st January 2020) - Burman, Yurii; Fröberg, Ralf; Shapiro, Boris
Abstract: In this paper we describe the algebraic relations satisfied by the harmonic and anti-harmonic moments of simply connected, but not necessarily convex planar polygons with a given number of vertices.